A Warm Layer in the Nightside Mesosphere of Mars. Issue 4 (17th February 2020) - Nakagawa, Hiromu; Jain, Sonal K.; Schneider, Nicholas M.; Montmessin, Franck; Yelle, Roger V.; Jiang, Fayu; Verdier, Loic; Kuroda, Takeshi; Yoshida, Nao; Fujiwara, Hitoshi; Imamura, Takeshi; Terada, Naoki; et al.
Abstract: We report a new set of stellar occultation measurements for nightside temperature profiles made by the Mars Atmosphere and Volatile EvolutioN/Imaging Ultraviolet Spectrograph that provide evidence for a recurring layer of warm air between 70 and 90 km altitudes in the nightside mesosphere of Mars during L s = 0–180° in Martian Year 33–34. The nightside profiles reveal a recurring peak of atmospheric temperature around 80 km over the equator to the middle latitudes in the northern hemisphere. The predictions of the Mars Climate Database have a warm layer with much smaller amplitudes. The observed peak amplitudes are larger than those predicted by the model by up to 90 K. Wavenumber‐3 structures are seen in the warm layer that are potentially signatures of thermal tides or stationary planetary waves, with amplitudes two times larger than predicted. Plain Language Summary: The Mars middle atmosphere is an intermediate region with rich and complex dynamics influenced by the underlying lower atmosphere and the overlying upper atmosphere. We report a new set of stellar occultation measurements made by the MAVEN/IUVS that provide evidence for a warm layer between 70 and 90 km altitude in the nightside mesosphere of Mars during L s = 0–180° in Marian Year 33–34. Key Points: MAVEN/IUVS revealed a warm layer between 70 and 90 km altitude in the nightside on Mars during L s = 0–180° in Martian Year 33–34 The observed peak temperature amplitudes of nightside profiles are higher than those predicted by the model by up to 90 K Longitudinal wavenumber‐3 structures are seen in the warm layer, two times larger amplitudes than predicted